Advancing Sustainability in Fruit and Vegetable Packaging: The Role of Nanotechnology in Food Preservation - Farhang Hameed Awlqadr; Ammar B. Altemimi; Ali Muhi Aldeen Omar; Mohammed N. Saeed; Syamand Ahmed Qadir; Aryan Mahmood Faraj; Alaa Jabbar Abd Al‐Manhel; Tablo H. Salih; Mohammad Ali Hesarinejad; Italo Rennan Sousa Vieira (eFood)
ABSTRACT Food packaging has seen a technological revolution through nanotechnology that provides highly innovative solutions to the increase of preservation, quality, and shelf life of fruits and vegetables. Moreover, this review has an in‐depth examination of the most advanced nanotechnology packaging that realizes a significant increase in barrier properties, it is involved in including antimicrobial method, and is a pioneer in making use of intelligent packaging systems. Different nanomaterials, such as nano‐coatings, nano‐films, and nanofibers have proven their effectiveness in modulating oxygen and moisture permeability and repressing microbial contamination along with systems for real‐time environmental monitoring. Furthermore, the incorporation of biodegradable nanocomposite films into the market provides a bio‐based alternative to conventional packaging, which is a cheaper and environmentally friendly way of maintaining food safety and freshness. However, despite such developments, it can be seen that there are a number of challenges that still require a bit further probing. The future research should concern the most comprehensive analysis of nanoparticles that migrate from the packaging into the products and how they may affect people in the case of long‐term exposure. Moreover, incorporating regulations related to the usage of nanotechnologies should be standardized to ensure that the adoption of nanotechnology in the food packaging process is safe and responsible. Green technology made the innovations in bio‐based nanomaterials and eco‐friendly nano‐coatings become a reality, which further promoted the sustainability of the gains and still brought all the benefits intact. Additionally, integrating smart packaging systems with nanosensors will offer the possibility of food waste reduction and improvement of supply chain efficiency through real‐time food quality monitoring. Continued interdisciplinary collaboration between food scientists, material engineers, and regulatory authorities will be crucial to addressing these challenges and unlocking the full potential of nanotechnology in food packaging.